New mariner elements in Anastrepha species (Diptera: Tephritidae) - Marcon, H. S. [UNESP]; Domingues, D. S.; Coscrato, V. E. [UNESP]; Selivon, D.; Perondini, A. L. P.; Marino, C. L. [UNESP] (Entomological Soc Brasil, 2011)
Mariner-like elements (MLE) are members from class II of transposable elements also known as DNA transposons. These elements have a wide distribution among different groups of organisms, including insects, which can be explained by horizontal and vertical gene-transfer. MLE families have been described in tephritid flies and other genera. During screening for Wolbachia bacteria in fruit flies of the genus Anastrepha, we discovered two sequences related to mariner-like elements. Based on these sequences, we designed primers that allowed us to isolate and characterize two new mariner-like elements (Anmar1 and Anmar2) in Anastrepha flies. These elements, which belong to the mellifera and rosa subfamilies have a low nucleotide diversity, and are probably inactive and acquired by vertical transfer. This is the first report of mariner-like transposons in flies found in South America.
Keywords: Fruit fly; mellifera; tephritid; transposon; rosa